Structure and quality assessment of professionally oriented tasks for future teachers - V. B. Veretennikova; O. F. Shikhova; Yu. А. Shikhov; A. A. Valeev; J. J. Mena Marcos (Russian State Vocational Pedagogical University, 2023)
Introduction. In recent decades, one of the significant global trends in the field of higher education is the expansion of its links with the world of work. This implies not only a new design of the results of training students in the form of a system of universal, general professional and professional competencies, but also the introduction of modern adequate technologies for assessing the level of their formation and development at all stages of students' education at a university. Given that competence is an integrative characteristic of personality traits, one should recognise the relevance and necessity of developing such assessment tools that create situations for the student to be included in various types of his/her future professional activities. One of these tools is professionally oriented tasks that allow for an integral approach assessing the formation of competencies by taking into account all types of professional tasks and broad interdisciplinary connections in their content and, therefore, requiring a synthesis of professional knowledge, skills and abilities of the student for their solution.Aim. The aim of the study is to justify the structure and criteria for assessing the quality of professionally oriented tasks to diagnose the level of student teachers' competency formation.Methodology and research methods. The methodological framework of the study was the activity, competency-based and qualimetric approaches, which allow the training of teachers to be considered as a flexible system that takes into account all types and tasks of their future professional activity, and reflects the relationship of goals, methods, content of training and diagnostics of its results. As the main one, the study used a qualimetric approach, which involves the use of the method of group expert assessments to organise procedures for pedagogical examination of the structure of professionally oriented tasks and criteria for assessing their quality.Results. The method of group expert assessments allowed the authors to define the structure and criteria for assessing the quality of professionally oriented tasks as a means of developing and diagnosing the integrative learning outcomes of future preschool teachers.Scientific novelty. The structure of professionally oriented tasks is substantiated, represented by: an invariant part with an emphasis on the fundamental component of the content of student training, covering the fundamental psychological and pedagogical knowledge of the future teacher, the ability to apply them synthetically and transfer them to professional activities; a variable component aimed primarily at diagnosing professional competencies determined by the profile of the student training. The criteria for assessing the quality of professionally oriented tasks have been established by the method of group expert assessments, which make it possible to objectify the procedures for diagnosing the competencies of future teachers: multifunctionality, specialisation orientation, latency, integrativity.Practical significance. The present research findings can be used by university teachers in the process of training and targeted correction of the readiness of pedagogical students. Moreover, the research materials could be applied to form and diagnose the entire spectrum of students' universal, general professional and professional competencies, including within the framework of possible individual educational trajectories.